Predicting occupancy and abundance by niche position, niche breadth and body size in stream organisms - Rocha, Mariana P.; Bini, Luis M.; Siqueira, Tadeu [UNESP]; Hjort, Jan; Grönroos, Mira; Lindholm, Marja; Karjalainen, Satu-Maaria; Heino, Jani (Springer Nature, 2018)
The regional occupancy and local abundance of species are thought to be strongly correlated to their body size, niche breadth and niche position. The strength of the relationships among these variables can also differ between different organismal groups. Here, we analyzed data on stream diatoms and insects from a high-latitude drainage basin to investigate these relationships. To generate measures of niche position and niche breadth for each species, we used sets of local environmental and catchment variables separately, applying the outlying mean index analysis. Beta regression and negative binomial generalized linear models were run to predict regional occupancy and mean local abundance, respectively. We found a positive occupancy–abundance relationship in both diatoms and insects, and that niche-based variables were the main predictors of variation in regional occupancy and local abundance. This finding was mainly due to local environmental niche position, whereas the effects of niche breadth on regional occupancy and local abundance were less important. We also found a relationship between body size and local abundance or regional occupancy of diatoms. Our results thus add to current macroecological research by emphasizing the strong importance of niche position rather than niche breadth and body size for regional occupancy and local abundance in rarely studied organisms (e.g., diatoms and insects) and ecosystems (i.e., wilderness streams).
Keywords: Algae; Distribution patterns; Insects; Occupancy–abundance relationship; Outlying mean index analysis